Can Ecotourism Succeed a Sustainable Livelihood: The Importance of Fishermen’s Involvement in Ciletuh Geopark - Dina Lianita Sari; Fitria Dewi Raswatie; Danang Pramudita; Leonita Dwiyanto; Akhmad Fauzi; Osmaleli (School of Business, IPB University (SB-IPB), 2021)
Ciletuh in Sukabumi area was inaugurated as a Global Geopark by UNESCO in 2017, and has many potential natural resources such as Palangpang Beach as a leading tourism area of Ciletuh Geopark. Palangpang Beach in Ciletuh Bay is also an estuary area used by fishermen to collect fish in Fish Auction (TPI). Fishermen on Palangpang Beach are categorized as small fishermen according to the size of the capture fishery units, which results in the fishermen on Palangpang Beach prefer to take part in tourist activities by chartering boats for tourists to increase their income. The objectives of the study were to investigate the impact of Geopark establishment on fishermen’s livelihood and to establish ecotourism development strategies in supporting the sustainable livelihood. The method used for sustainable livelihood analysis was descriptive analysis. The results showed that increased sustainable livelihood assets of fishermen were found in human capital, social capital, physical capital, and economic and financial capital, while natural capital assets declined. The Geopark Ciletuh development strategy to improve the sustainable livelihood can be performed through the fishermen involvement in capture fishery and Geopark tourism management such as by becoming a tour guide, a fishing trainer, an educator who educates on fishing weather in fisheries, a mangrove planter, and a coral reef educator. Keywords: capital asset, geopark, descriptive analysis, ecotourism, fish auction